Recombinase Polymerase Amplification/Cas12a-Based Identification of Xanthomonas arboricola pv. pruni on Peach - Luo, Mei; Meng, Fan-Zhu; Tan, Qin; Yin, Wei-Xiao; Luo, Chao-Xi (Frontiers in Plant Science, 2021)
Peach bacterial spot caused by Xanthomonas arboricola pv. pruni (Xap) is a devastating disease worldwide and frequently causes massive economic losses. In recently years, it has become a pandemic outbreak in most peach production areas of China, especially on precocious peaches in the middle reach of the Yangtze River. A rapid, user-friendly detection is extremely important to make correct diagnosis and develop suitable control strategies. Here, we described a RPA/Cas12a-based system that combined recombinase polymerase amplification (RPA) and CRISPR/Cas12a for Xap identification. A total of 3 crRNAs were designed to target a highly conserved specific gene ftsx to make specific detection of Xap. Results showed that the crRNA 2 and crRNA 3 could get consistent detection for Xap. In order to realize the visualization of detection results, we additionally introduced FQ-reporter and FB-reporter. The developed method was highly sensitive and could detect as low as 10-18 M Xap gDNA with a mini-UV torch, corresponding to 1.63 copies/µL or 8.855 fg/µL gDNA of Xap, while with lateral flow strips, the sensitivity was 10-17 M. In addition, this method could specifically detect Xap from other closely related bacteria or pathogens associated with peach diseases. Furthermore, this method could make correct identification for Xap with crude DNA using NaOH-based extraction (3 min) directly from diseased peach samples. Considering that the developed method could get results within 2 hrs and could be performed at 37℃ (body temperature), it is promising to be applied for Xap diagnosis and monitoring in fields.